TYROSINE AMMONIA LYASE EXTRACTED FROM CLITORIA TERNATEA LINN. - ITS IMPORTANT ROLE IN METABOLISM OF HUMANS AND REACTION WITH DIFFERENT METAL IONS - GURUPRASAD R,; DEEPASHREE H R,; MANASA B,; SOUNDARYA S P, (International Journal of Pharma and Bio Sciences, 2014)
Tyrosine ammonia lyase (TAL; EC 4.3.1.23) is an enzyme required for deamination of the amino acid L-tyrosine to p-coumaric acid (B.E. Ellis et al., 1973).The enzyme TAL was extracted from the plant Clitoria ternatea linn. This enzyme can be used in the treatment of an autosomal recessive metabolic disorder tyrosinemia type II where tyrosine is accumulated in excess amounts in the body. The extraction of this enzyme was based on two techniques: Firstly, the separation of proteins using an organic solvent, acetone. In the second step, the presence of enzyme is to be detected hence standardization of the enzyme assay was accomplished. The presence of the enzyme was confirmed by the formation of p-coumaric acid which was detected by using UV-Visible spectrophotometer at 333nm. Also, the activity of the enzyme was enhanced using an activator –nickel sulphate, an inorganic salt.